EFFECT OF STEM TIP EXCISION, SPRAYING WITH BENZYLADENINE AND CYCOCEL ON FLOWERING OF TWO CULTIVARS OF Gerbera jamesonii - A. Atrakchii; H. AL- Qarakolly (Mesopotamia Journal of Agriculture)
This study was carried out in the College of Agriculture and Forestry, Mosul University, between February and November/2006 on Gerbera jamesonii cv. Esstafette (red inflorescence) and Essandre (yellow inflorescence), to investigated the effect of stem tip excision and spraying plants with benzyl adenine (BA) at 0, 250 and 500 mg.l-1 or Cycocel (CCC) at 500 and 1000 mg.l-1 separately, on flowering character. The factorial experiment was conducted by using randomized complete block design, each treatment was replicated three times with four plants in block. The results can be summarized as follows: Inflorescence taken from Essandre plants recorded higher values of diameter 76.50 mm, while Estafette inflorescences recorded longest peduncles 34.32 cm, and dry weight of peduncles.Stem tip excision plants caused a significant decrease of inflorescences number, diameter, and dry weight, in addition to peduncle diameter, and scape dry weight. Spraying plants with BA at 500 mg.l-1 gave a significant increase in inflorescences number 5.52 inflorescence/plant, and dry weight of inflorescence 8.63 and 1.71 g, respectively in addition to peduncle length, and scape dry weight when compared with control. Treated non-pinched plants with BA at 250 and 500 mg.l-1 gave higher number of inflorescences 6.59 and 6.82 inflorescences/plant for Estafette cultivars, respectively and for Essandre cultivars 5.87 and 6.00 inflorescences/plant respectively. Furthermore, the treatments above pointed to the best results of other inflorescences characters for two cultivars.